KNOWLEDGE ABOUT COVID-19 VACCINE IN COMMUNITY: CROSS SECTIONAL STUDY - Mahdaniah Mahdaniah; Nurul Mardiati; Wahyudi Wahyudi (Jurnal Riset Kesehatan, 2022)
COVID-19 is an infectious disease that spreads through fluids when the infected person coughs or sneezes. Vaccination is one of the effective ways to prevent COVID-19. Good knowledge of COVID-19 vaccines will increase the willingness of people to get vaccinated. If the vaccination program is successful, it can reduce and prevent the transmission of COVID-19. Sociodemographic characteristics like education and income are significantly related to a person's knowledge of COVID-19 vaccination. The study aims to determine the relationship between the sociodemographic characteristics with the knowledge of the COVID-19 vaccine in the community of Banjar Regency. This study used a cross-sectional design and a descriptive-analytic analysis. There are 400 samples used and obtained using an accidental sampling technique. In the data analysis, univariate and bivariate analysis was used with the chi-square test. It found that the level of public knowledge of the COVID-19 vaccine in the Banjar Regency area is poor knowledge (40.3%) of the COVID-19 vaccine. There is a relationship between gender, age, education, income, and sources of knowledge about the COVID-19 vaccine in the community of Banjar regency.